2014
DOI: 10.1242/jcs.136259
|View full text |Cite
|
Sign up to set email alerts
|

RAGE signaling deficiency in rhabdomyosarcoma cells causes upregulation of PAX7 and uncontrolled proliferation

Abstract: BSTRACTEmbryonal rhabdomyosarcomas (ERMSs) show elevated levels of PAX7, a transcription factor that marks quiescent adult muscle stem (satellite) cells and is important for proliferation and survival of activated satellite cells and whose timely repression is required for myogenic differentiation. However, the mechanism of PAX7 accumulation in ERMSs and whether high PAX7 causes uncontrolled proliferation in ERMS remains to be elucidated. The receptor for advanced glycation end-products (RAGE, encoded by AGER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…RAGE has emerged as a promyogenic cell surface receptor playing a key role in promoting cell cycle exit and differentiation in muscle precursor and ERMS cells (8)(9)(10)(11)14). Here we show that ectopic expression of RAGE in TE671 ERMS cells translates into reduced ability to metastasize lungs following i.p.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…RAGE has emerged as a promyogenic cell surface receptor playing a key role in promoting cell cycle exit and differentiation in muscle precursor and ERMS cells (8)(9)(10)(11)14). Here we show that ectopic expression of RAGE in TE671 ERMS cells translates into reduced ability to metastasize lungs following i.p.…”
Section: Discussionmentioning
confidence: 71%
“…Immunofluorescence analyses confirmed that myoblasts transfected with PAX7 were characterized by undetectable levels of NCAM, whereas high fluorescence for NCAM was found in cells overexpressing myogenin ( Figure 5C). Because myogenin reduces PAX7 levels and vice versa (14), in order to assess whether myogenin or PAX7 is responsible for the observed changes in NCAM levels we knocked down either Myog, Pax7 or both in WT primary myoblasts in DM. We found that NCAM mRNA and protein levels correlated negatively with PAX7 and showed no correlation with myogenin levels in the experimental conditions tested ( Figure 5D and E), suggesting that a repressor activity of PAX7 rather than a stimulatory activity of myogenin is involved in the regulation of NCAM expression in muscle precursor cells.…”
Section: Myogenin Causes Pax7 Downregulation Which Results In Ncam Inmentioning
confidence: 99%
See 3 more Smart Citations